2008
DOI: 10.1261/rna.1221108
|View full text |Cite
|
Sign up to set email alerts
|

Experimental identification of microRNA-140 targets by silencing and overexpressing miR-140

Abstract: MicroRNAs (miRNAs) are short noncoding RNA molecules regulating the expression of mRNAs. Target identification of miRNAs is computationally difficult due to the relatively low homology between miRNAs and their targets. We present here an experimental approach to target identification where the cartilage-specific miR-140 was overexpressed and silenced in cells it is normally expressed in separate experiments. Expression of mRNAs was profiled in both experiments and the intersection of mRNAs repressed by miR-140… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 35 publications
2
99
0
Order By: Relevance
“…We recently generated mRNA expression profiles of C3H10T1/2 cells following overexpression or suppression of miR-140 (Nicolas et al 2008). This approach identified several direct miR-140 targets that showed higher or lower mRNA levels when the miRNA was silenced or overexpressed, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We recently generated mRNA expression profiles of C3H10T1/2 cells following overexpression or suppression of miR-140 (Nicolas et al 2008). This approach identified several direct miR-140 targets that showed higher or lower mRNA levels when the miRNA was silenced or overexpressed, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Several target genes of miR-140 have been identified recently including histone deacetylase 4 (Tuddenham et al 2006), platelet-derived growth factor receptor a (Eberhart et al 2008), CXC group of chemokine ligand 12 (Nicolas et al 2008), and Smad3 is another biologically relevant target gene. The Smad transcription factor family is part of the TGFb pathway (Heldin et al 1997), which plays a role in many diverse biological processes including chondrogenesis and chondrocyte differentiation (Yang et al 2001).…”
Section: Identification and Validation Of Smad3 As A Mir-140 Targetmentioning
confidence: 99%
See 2 more Smart Citations
“…4 6 The subset of miRNA targets that are destabilized in vivo can be identified as downregulated upon induction of the targeting miRNA and vice versa using microarray, qPCR-based or sequencing approaches. [9][10][11][12] miRNAs are implicated in many cancers 13 and have been shown to be useful as biomarkers. 14 The exposure of human cells in tissue culture to various stresses has shown that miRNAs respond to a diversity of external stimuli, 15 indicating important regulatory roles in cellular responses to stress.…”
mentioning
confidence: 99%